Angle's Class II division 1 associated to mandibular retrusion and skeletal open bite: a 5-year post-orthodontic/orthopedic treatment follow-up - Gustavo Tirado Rodrigues
ABSTRACT Obtaining long term stability allied to functional and aesthetic balance is the main goal of any orthodontic-orthopedic therapy. This case report describes the orthodontic therapy applied to a 7-year-9-month old child, who presented a Class II, division 1 malocclusion associated to skeletal open bite. Functional and skeletal corrections (sagittally and vertically) were obtained by means of mandible advancement achieved with a closed Balter's bionator appliance followed by a fixed appliance. This approach showed to be efficient in accomplishing both functional and aesthetic goals, that were kept stable five years after the treatment was finished. This case report was presented to the Board of Directors of the Brazilian Board of Orthodontics and Facial Orthopedics (BBO), as partial requirement to becoming a Diplomate of the BBO.